Subclinical hyperthyroidism: to treat or not to treat?. Issue 945 (14th July 2004) - Hoogendoorn, E H; den Heijer, M; van Dijk, A P J; Hermus, A R
Abstract : Subclinical hyperthyroidism may be defined as the presence of free thyroxine and tri-iodothyronine levels within the reference range and a reduced serum thyroid stimulating hormone (TSH) level. In this review the prevalence of low TSH in the population and health consequences of subclinical hyperthyroidism, for example, effects on heart and bone mass, are discussed. Guidelines for treatment are given, based on expert opinion.